Assessment of the efficacy of autologous blood preparations in maxillary sinus floor elevation surgery: a systematic review and meta-analysis - Piaopiao Qiu; Xuehan Zhang; Rongkai Cao; Hui Xu; Zihan Jiang; Jingshi Lei (BMC, 2024)
Abstract Objective This study aimed to evaluate the efficacy of autologous blood preparations, namely Platelet-Rich Plasma (PRP), Platelet-Rich Fibrin (PRF), and Concentrated Growth Factor (CGF), in maxillary sinus floor elevation surgery. The focus was on their impact on new bone formation, maxillary sinus floor height, and soft tissue healing. Methods A systematic search was conducted across PubMed/MEDLINE, Web of Science, Embase, and Scopus databases up to April 2024. This systematic review included both randomized clinical trials (RCTs) and controlled clinical trials (CCTs) that evaluated the efficacy of autologous blood preparations in maxillary sinus floor elevation surgery. The primary outcomes measured were the percentage of new bone formation, maxillary sinus floor height, and he percentage of soft tissue area. Data from the selected studies were extracted and analyzed to determine the impact of autologous blood preparations on these outcomes. The risk of bias was assessed using Cochrane's risk of bias tool and ROBINS-I, and meta-analyses were performed using Review Manager 5.4 software to calculate effect sizes and integrate results from multiple studies. Results Among the 507 screened articles, 30 studies met the inclusion criteria. The results indicated that the application of PRP significantly increased new bone formation during maxillary sinus floor elevation surgery (primary outcome, MD = 4.40, CI = 0.37 to 8.44, P = 0.03), as well as improving maxillary sinus floor height elevation (secondary outcome, MD = 1.00, CI = 0.78 to 1.23, P < 0.00001). The absence of PRP during surgery had a statistically significant effect on the percentage of soft tissue area (secondary outcome, MD= -5.25, CI= -7.29 to 3.20, P < 0.00001). However, based on the research findings, PRF did not show significant effects on enhancing new bone formation, maxillary sinus floor height elevation, and promoting soft tissue regeneration. Conclusions PRP demonstrates efficacy in maxillary sinus floor elevation surgery by enhancing new bone formation and increasing sinus height. Further studies are needed to validate the outcomes of PRF and CGF.